Educating in times of globalization (II) (Journal of Parents and Teachers, 2014)
The main objectives of education are "learning to know", "learning to learn", "learning to live together" and "learning to be", depending on the figure of the teacher. Keeping these and today's society in mind, we seek to get to know the students and their culture, control the instruments for their correct application and communicate appropriately to express ideas, content or feelings. For this reason, it emphasizes getting a good relationship with them and with their families, to attend to their reality and their characteristics in a particular and sensitive way. In other words, acting on the ideas and desires of our students to achieve their correct growth and development.
Keywords: Globalization; ethics; virtuosity; ICT; sensitivity; education; students; culture; communication